Pengaruh Influencer Jktdelicacy Terhadap Minat Penggunaan Aplikasi Fami Apps - Elmalia Putri; Jamiati KN (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
by Family Mart at the time of release The new application is Fami Apps. The strategy used by Family Mart is by collaborating with influencer @jktdelicacy to promoteFami Apps. Influencer @jktdelicacy made a video about the Fami Apps application which was posted on Family Mart's Instagram social media. Related to this goal This research is to find out how much influence influencers have @jktdelicacy on followers of the Instagram account @familymartid. The theory used in this research, namely Influencers which include credibility, attractiveness and power. For interest in use, it includes transactional interest, interest referential, preferential interest, exploratory interest. Approach in this research is to use quantitative survey methods. Data collection technique in this study was to distribute questionnaires randomly to 83 respondents, with the criteria for followers of the Instagram account @familymartid. The results of this study shows that the influence of the influencer @jktdelicacy as a whole respondents responded either or (agree), as well as the influence of influencers on interest Overall usage respondents responded good or (agree). Of all statements contained in this research, and the magnitude of the influence of influencers has a strong relationship of 0.808 to interest in using followers Instagram @familymartid. The results of this research show that the influence Influencer @jktdelicacy overall respondents responded well (agree), with the percentage of influencer interest influencing usage interest by 65.2% and the remaining 34.% is influenced by other factors.